Using recombinant human G-CSF to treat chemotherapy-induced neutropenia over 3 decades: What is next? - Jason Xu; Jonathan Sussman; Jessica Xu; Xing Zhao; Xiao Qiang Yan (Annals of Bone Marrow Research - Peertechz Publications, 2023)
Chemotherapy-Induced Neutropenia (CIN) is a potentially fatal side effect of cancer treatment, affecting > 50% of cancer patients treated with chemotherapy. Clinical use of recombinant human granulocyte colony-stimulating factor (rhG-CSF) has allowed for primary and secondary prophylaxis of CIN and its sequela (i.e., febrile neutropenia, fatal infection) during myelosuppressive chemotherapy. Here, we review the translation and properties of first, second, and third-generation rhG-CSF molecules, including filgrastim (Neupogen, FDA approved in 1991) and biosimilars, pegfilgrastim (Neulasta, FDA approved in 2002) and biosimilars, and F-627 (Ryzneuta, NMPA approved in 2023), a novel long-acting rhG-CSF agent developed this past decade. Even with the development of increasingly personalized and targeted cancer therapy, chemotherapy, and stem cell transplantation remains a backbone for the majority of patients with advanced cancers, especially in the hematopoietic system. As such, more than 20 million cancer patients have been treated with rhG-CSF drugs since the first approval of filgrastim. In the next decade, we envision third-generation rhG-CSF products such as Ryzneuta lowering costs to patients and healthcare providers, expanding access to this essential medication for cancer patients worldwide, particularly for patients who require more aggressive chemotherapy treatment.